Environmental geology - Montogomery, Carla W. (Boston, Massachusetts : McGraw Hill Education, 2003)
Intended for the introductory-level college course, the principal aim of this text is to present the student with a broad overview of environmental geology. The text looks both at how the earth developed into its present condition and where matters seem to be moving for the future.-publisher description.